2015
DOI: 10.2136/vzj2014.07.0088
|View full text |Cite
|
Sign up to set email alerts
|

Hysteresis in the Soil Water Retention of a Sand–Clay Mixture with Contact Angles Lower than Ninety Degrees

Abstract: Soil water retention curves (SWRCs) are usually obtained on the assumption small water menisci spread in the surface of particles yielding contact angles near zero degrees. While this is true at high water contents, where pores are filled by water or a film of water covers the particles, it is less likely for drier states, where the adhesion of water menisci to the surface of the particles is controlled by the nature of the particle surface (chemistry and surface roughness) and the presence of organic matter. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 21 publications
(29 reference statements)
2
15
0
Order By: Relevance
“…Notably, hydrophilic and water-repellent retention curves were similar in the low (<AEV) and high (greater than residual) suction ranges. Similar results were found by [16] and [18]; lower gravimetric water contents were found for hydrophobised granular soils than for the same soils in a hydrophilic condition for a given suction. Possible desaturation mechanisms for a hydrophilic and water repellent granular soil are shown schematically in Figure 3.…”
Section: Macroscopic Levelsupporting
confidence: 86%
See 3 more Smart Citations
“…Notably, hydrophilic and water-repellent retention curves were similar in the low (<AEV) and high (greater than residual) suction ranges. Similar results were found by [16] and [18]; lower gravimetric water contents were found for hydrophobised granular soils than for the same soils in a hydrophilic condition for a given suction. Possible desaturation mechanisms for a hydrophilic and water repellent granular soil are shown schematically in Figure 3.…”
Section: Macroscopic Levelsupporting
confidence: 86%
“…Notably, tested soils in [16] to [18] displayed positive suctions. Soils in [17] were not tested in wetting, which is more likely to produce higher contact angles.…”
Section: Macroscopic Levelmentioning
confidence: 99%
See 2 more Smart Citations
“…Lourenço et al [5] demonstrated that for a mixture of sand and clay, its ability to retain water decreased as the ACA approached 90. Shear strength of non-wettable soils as evaluated by direct shear tests performed by Bardet et al [6] using soils coated by wax demonstrated that there was no change in the angle of shear resistance compared to wettable samples.…”
Section: Introductionmentioning
confidence: 99%